2019
DOI: 10.1001/jamaophthalmol.2019.0868
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, Genetic, and Demographic Factors Associated With Conversion to Neovascular Age-Related Macular Degeneration

Abstract: IMPORTANCE Risk factors associated with the development of neovascular age-related macular degeneration (AMD) have been identified. However, population size and methods to integrate imaging, genetic, and demographic factors associated with conversion to neovascular AMD are limited, specifically when treatment is administered in 1 eye. OBJECTIVE To determine the imaging, genetic, and demographic factors associated with conversion from nonneovascular to neovascular AMD in fellow eyes. DESIGN, SETTING, AND PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…Our study found that in low-HDI areas, people had a higher global AMD health burden, and females had a higher burden than males. A study conducted in Chicago was consistent with our ndings, suggesting that more women had converted to neovascular AMD than men [41], resulting in a higher global AMD burden. However, in our results, the global AMD burden of veryhigh-HDI countries did not show the same regularities (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that in low-HDI areas, people had a higher global AMD health burden, and females had a higher burden than males. A study conducted in Chicago was consistent with our ndings, suggesting that more women had converted to neovascular AMD than men [41], resulting in a higher global AMD burden. However, in our results, the global AMD burden of veryhigh-HDI countries did not show the same regularities (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The total number of drusen or measured drusen area or volume, are risk factors for the progression to GA and nAMD . Also, the location of the drusen is of predictive value for disease progression, since eyes with drusen near the fovea have a higher probability of developing late AMD compared to eyes with drusen outside the fovea . Although CFP is useful for assessing the appearance of drusen, multimodal imaging can be used to distinguish subtypes of drusen …”
Section: Phenotypic Risk Factorsmentioning
confidence: 99%
“…There are many modifiable and non‐modifiable risk factors that have been linked to increased risk of the progression of AMD. As the name already suggests, age is the most important demographic risk factor for AMD . A recent meta‐analysis, combining data of 14 population‐based studies, showed an increase in the prevalence of early AMD from 3.5% in people aged 55–59 years up to 17.6% in people 85 years and older.…”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 99%
“…Previous studies have suggested potential functions for ACAD10 protein in the central nervous system, metabolism, and immunity, but no functional studies were performed [ 7 ]. A randomized clinical trial has identified an association of an ACAD10 variant with neovascular age-related macular degeneration (AMD) [ 9 ]. We recently have characterized an Acad10 gene trap knockout mouse model [ 7 ].…”
Section: Introductionmentioning
confidence: 99%